Features of Criticism in Koshke Kemengerov’s Journalism - Batkeyeva Б.Т. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2019)
The talented writer Koshke Kemengerov also drew attention to literary criticism. One of those who gave fair assessment to poets and writers was Koshke. In the twentieth century there has been controversy in fiction. In 1926, in the newspaper Enbekshi Kazakh, Mukhtar Auezov, Koshke Kemengerov, Ergali Aldongorov, Abdrakhman Baidildin, Mazhit Dauletbaev, Sabit Mukanov and other famous writers and literary writers took part in these disputes. The article reveals the essence of the discourse of the famous public figure and writer Koshke Kemengerov, and his work is evaluated objectively